Computer Simulations of the Band Structure and Density of States of the Linear Chains of NaCl Ions - Myasnikova, L.N.; Istlyaup, A.S.; Sergeyev, D.M.; Zhanturina, N.N.; Shunkeyev, K.Sh.; Popov, Anatoli I. (Sciendo, 2019)
The paper presents the results of first-principles computer simulations of the band structure, the density of states, and the total energy of NaCl (NaCl, Na2Cl2, Na3Cl3, Na4Cl4, Na6Cl6) linear chains of atoms. Modelling of the specified characteristics is realised in the computer code Atomistix ToolKit combined with Virtual NanoLab. The total energy depends on the number of ions in the nanoobject under study, but practically does not depend on the geometric arrangement of ions.
The authors thank Eugene Kotomin and V. Kuzovkov for fruitful discussions and valuable suggestions. A.I.P thanks A.Moskina for the technical assistance in preparation of the manuscript. A.I.P also gratefully acknowledges a project LZP-2018/1-0214 from the Latvian Council of Science for partial support.
Keywords: band structure; computer simulations; density of states; NaCl; total energy; Research Subject Categories::NATURAL SCIENCES:Physics